Evaluating the Impact Of Digital Pathology And AI On Diagnostic Accuracy And Workflow Efficiency In Pathology Laboratories. - Momina Khadija Abbasi, Nosheen Ali Khan, Sabahat Rehman, Sadia Israr, Nazia Siddiqui, Maliha Ansari (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background : Whole-slide imaging or digital pathology in which the conventional tissue slides are digitized and AI or artificial intelligence, which uses neural networking, is inciting a shift in pathology. The above innovations seeks to increase the diagnostic accuracy and efficiency, challenges that are experienced in the traditional methods of manual slide review and data management.